Torrefaction of de-oiled Jatropha seed kernel biomass for solid fuel production - Gan, Yong Yang; Ong, Hwai Chyuan; Ling, Tau Chuan; Chen, Wei-Hsin; Chong, Cheng Tung (Elsevier, 2019)
Non-edible Jatropha seed used for biodiesel production has increased due to its high-oil contents in kernel and potential to reduce greenhouse gas emission. High demand for biodiesel generates a large volume of waste. In this study, de-oiled Jatropha seed kernel was torrefied at 200 °C, 250 °C and 300 °C, holding time of 15, 30, 45 and 60 min and particle sizes of 0.5–1.0 and 1.0–2.0 mm to produce solid fuel. Torrefaction performance was highly affected by torrefaction temperature compared with holding time. The enhancement factor of HHV increased up to 1.243 after torrefaction at 300 °C and 60 min with particle size of 0.5–1.0 mm. The large particle size reduces the diffusion rate of torrefaction vapour through internal pores, thereby producing high solid yield and low enhancement in HHV. The analysis of torrefaction severity index shows that HHV increase is highly dependent on the weight loss, thereby directly decreasing the total energy in biochar. Scanning electron microscopy image clearly illustrated that the microparticles on the surface were destroyed to increase the porous structure of the biochar with increasing torrefaction temperature. Severe torrefaction with particle size of 0.5–1.0 mm was an effective approach to increase the energy content of biochar.